Design and Characterization of Camptothecin Loaded Colloidosomes for the Effective Treatment of Lung Cancer - Harale, Swapnil; Mirajakar, Kaivalya; Galatage, Sunil; Manjappa, Arehalli; Patil, Mrityunjaya; Sutar, Kishori; Katkar, Rushikesh; Bhagwat, Durgacharan; Potti, Lakshmanarao; Trivedi, Rahul; Kandukuri, Gourisankar; Kumbhar, Prajyot; et al. (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Among the various cancers, lung cancer is the second leading cause of mortality after the breast carcinoma. Camptothecin (CPT) has broad spectrum anticancer potential used in the effective management of cancer including lung cancer. However, the therapeutic applications of CPT in the clinics are restricted due to its poor water solubility, low bioavailability and severe toxicities. Therefore, current research work was aimed to develop, optimize and characterize colloidosomes for safe and efficient delivery of CPT against lung cancer. Materials and Methods: Colloidosomes were prepared by using oil-in-water emulsion-based method and optimized using 32 Factorial design using sodium alginate as emulsifier and calcium carbonate as stabilizer. The optimized CPT Colloidosomes were lyophilized using freeze dryer and characterized for morphology by Transmission Electron Microscope (TEM), crystallinity by X-ray Diffraction (XRD), in vitro release, in vitro cytotoxicity, apoptotic potential etc. Results: The batch S9 has displayed high % entrapment efficiency (95±1.49%) and less particle size (327±9 nm and PDI: 0.267±0.019); therefore, it is selected as optimized batch. Besides, colloidosomes exhibited zeta potential of -24.5±3.2 mV revealing better stability. Further, the surface morphology results confirmed the self-assembling nature of colloidosomes which are spherical in shape. Moreover, lyophilized CPT Colloidosomes displayed sustained and maximum release of CPT (98±4.5%) after 8hr in PBS (Phosphate buffer solution) pH 7.4. Furthermore, the colloidosomes demonstrated significantly (p<0.01) higher in vitro cytotoxic and apoptotic activity against lung cancer (A549) cells after 48 hr of incubation. Conclusion: Results obtained revealed the remarkable in vitro anticancer potential of CPT in the form of colloidosomes which can further alleviate the side effects caused by systemic therapy of CPT. However; further in vivo animal studies are required to establish its efficacy treatment of lung cancer.
Keywords: Apoptosis; Camptothecin; Colloidosomes; Cytotoxicity; Lung cancer; Optimization.